Chemical modifications, characterization and properties of carboxymethyl cellulose filled halloysite nanotube bio-nanocomposite films - Suppiah, Kathiravan (School of Materials Engineering, 2019)
This research focused to study the effect of CMC and HNT content and different types of chemical modifications of the CMC/HNT bio-nanocomposite films. Different tests and characterizations were performed to study the properties of CMC/HNT bio-nanocomposite films. The measurement of Young's modulus, tensile strength and elongation at break of bio-nanocomposites were studied using tensile test. Thermal properties of the CMC/HNT bio-nanocomposite films were measured using thermogravimetric analysis (TGA). The morphology studies of the bio-nanocomposites were investigated using field emission scanning electron microscope (FESEM). Meanwhile, the moisture content test was used to determine the amount of water in both untreated and treated CMC/HNT bio-nanocomposite films. The functional groups of untreated and treated CMC/HNT bio-nanocomposite films were also examined using FTIR test. The X-ray diffraction (XRD) was used to measure the diffraction angle of the peaks and basal spacing of the bio-nanocomposites.